ANALISIS SISA PEMBAGIAN DARI SIGMA 13i PANGKAT m DENGAN i DARI 1 SAMPAI n OLEH PEMBAGI 2 - Satria Riki Mustafa (Jurnal Edu Research, 2020)
Divisibility of finite sums of power of integers such as , , and has been developed by authors in some books and articles. In this article will be discussion residual of result division divisible by two by using divisibility concept and formulate it based on residual of result division that is listed into tables.